The SAGE encyclopedia of action research - Coghlan, David; Brydon-Miller, Mary (Los Angeles : SAGE, 2014)
This encyclopedia brings together the many strands of action research and addresses the interplay between these disciplines by presenting a state-of-the-art overview and comprehensive breakdown of the key tenets and methods of action research as well as detailing the work of key theorists and contributors to action research.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Action research -- Encyclopedias